Economia de polêmicas: uma análise da emergência das mobilizações antigênero no Brasil e no Paraguai - Ferreira, Camila Camargo (Universidade Federal de São Carlos, 2023)
During the 2010s, transnational mobilizations of conservative groups emerged in opposition to the demands of feminist and LGBTQIA+ movements (including lesbian, gay, bisexual, transgender, queer, intersex, and other gender and sexual identities), with their actions anchored in the politicization of the concept of "gender ideology." This thesis examines the formation and consolidation of activism against so-called gender ideology in Brazil and Paraguay throughout this decade. Its objective is to comparatively analyze the transnational characteristics and dynamics of anti-gender activism, focusing on the identification of actors, forms of action, discursive frameworks, and the worldviews constructed. This research aims to contribute to the expanding field of comparative studies on anti-gender mobilizations. To analyze this phenomenon, it employs theories of collective action, gender and sexuality studies, alongside scholarly work on the anti-gender phenomenon. Utilizing a qualitative approach, this study adopts document analysis and digital media research as investigative techniques. Findings indicate that, in both Brazil and Paraguay, anti-gender mobilizations were organized through coordinated actions among national and transnational pro-life and pro-family actors and entities. Data analysis further reveals that anti-gender activism emerges from a complex network of mobilization that interconnects conservative actors across national and transnational spheres.
Economy of polemics: a study of the emergence of anti-gender mobilizations in Brazil and Paraguay
Keywords: Ações coletivas; Antigênero; Ativismo conservador; Direitos sexuais e reprodutivos; Políticas sexuais; Collective action; Anti-gender; Conservative activism; Sexual and reproductive rights; Sexual politics; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS